PTU-065 The influence of smoking on need for surgery and post-operative outcomes in crohn's disease. (22nd June 2015) - O'Connor, A; Taylor, J; Abid, F; Crudeli, A; Clark, T; Scott, N; Hamlin, PJ; Ford, AC
Abstract : Introduction: Up to 70% of patients with Crohn's disease (CD) may require surgery at some point in their lives and it is estimated 39% may require several surgeries. Indications for surgery include failure of medical treatment, bowel obstruction, fistula or abscesss formation. The most common surgical procedure is resection. Smoking is a recognised risk factor for requiring surgery in Crohn's and also predicts post-operative recurrence. Method: We aimed to examine the effect of tobacco smoking on the risk for surgery and it's influence on post-operative outcomes in patient with CD. We performed a retrospective analysis by initially identifying cases by interrogating the pathology database over a five year period from 2009 to 2013 and further data was then extracted by chart review. Results: 152 resections took place over the study period, 6 of these had taken place on children and these were not analysed for smoking history. Median follow-up was 32 months (range 1 to 69 months). 31.5% (n = 46) of adults were active smokers at time of surgery. Among those having repeat resections 24.1% were active smokers. Smokers were more likely to have required emergency surgery than non-smokers (34.8% vs 30.0%). Median disease duration prior to surgery (among patients having first surgery) was shorter in the smoking group (2.5 vs 4 years). Smokers were more likely to have penetrating disease (32% vs 25.5%). The rate of steroid-free, further resection-free survival at end of follow up was higher for non-smokers (66% vs 63.0%). 68 patients had colonoscopies during follow-up, in 4 cases a Rutgeerts score could not be ascertained from the report. 43.8% (7/16) of smokers had endoscopic recurrence with Rutgeerts score i2 or greater compared to 45.8% (22/48) of non-smokers. Conclusion: Compared to the background rate of smoking among adults in the UK (18.7%), smokers are over-represented in this CD surgery cohort. In this small, retrospective cohort smokers were more likely to have penetrating disease, come to surgery sooner and require emergency surgery than non-smokers. Outcomes were broadly similar for smokers and non-smokers with a minor benefit for achieving steroid free, further resection-free survival in the non-smoking group and slightly less endoscopic recurrence among smokers. The lower rate of smoking among those having repeat resections compared to first resections may indicate that a CD resection is a motivating factor to give up smoking. Disclosure of interest: None Declared.